2018
DOI: 10.1016/j.hpb.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization plus iodine-125 implantation for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Based on these findings, TACE plus iodine-125 implantation achieves better clinical efficacy compared with TACE alone in the treatment of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Previous studies reported that TACE conferred significant survival benefits or reduced tumor growth in patients with HCC, 21,22 with a notable effect on 2-year survival. 23 A meta-analysis 24 of nine studies reported significantly higher 1-year OS (odds ratio [OR]: 4.72, 95%CI: 2.63, 8.47, P < 0.001) and 2-year OS (OR: 4.72, 95%CI: 2.63, 8.47, P < 0.001) in patients treated with TACE–iodine-125 compared with TACE alone. The results of the current study similarly showed that patients with HCC (≤5 cm) treated with TACE–iodine-125 particle implantation had longer median PFS (16 months vs 8 months, P < 0.001) and OS (42 months vs 23 months, P = 0.005) than those treated with TACE alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that TACE conferred significant survival benefits or reduced tumor growth in patients with HCC, 21,22 with a notable effect on 2-year survival. 23 A meta-analysis 24 of nine studies reported significantly higher 1-year OS (odds ratio [OR]: 4.72, 95%CI: 2.63, 8.47, P < 0.001) and 2-year OS (OR: 4.72, 95%CI: 2.63, 8.47, P < 0.001) in patients treated with TACE–iodine-125 compared with TACE alone. The results of the current study similarly showed that patients with HCC (≤5 cm) treated with TACE–iodine-125 particle implantation had longer median PFS (16 months vs 8 months, P < 0.001) and OS (42 months vs 23 months, P = 0.005) than those treated with TACE alone.…”
Section: Discussionmentioning
confidence: 99%
“…ISI implantation has been gradually developed in clinical practice as a new, minimally invasive treatment for unresectable HCC therapy. Previous studies have shown that TACE combined with ISI permit to control liver tumors by local therapy, which is beneficial for patients [ 11 , 12 ]. Basic experimental studies have confirmed that 125 I seed implantation control tumors mainly through apoptosis and G2/M cell cycle arrest [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-125 ( 125 I) seed implantation (ISI) is being increasingly used as a minimally invasive treatment and in the treatment of intrahepatic and extrahepatic tumors, as it has been shown to achieve a better effect [ 9 , 10 ]. Combined TACE treatment for HCC can result in prolonged survival [ 11 , 12 ]. To our knowledge, the ISI after TACE treatment of local residual HCC or CCC tumors in challenging locations has limited coverage in the literature.…”
Section: Purposementioning
confidence: 99%
“…Typically, in the treatment of HCC, the implantation of iodine 125 seeds is combined with other treatment modalities, such as RFA or surgery [16,17]. It has been demonstrated that the combined treatment of TACE with iodine 125 seeds implantation (TACE-Iodine 125) provides a longer survival time than TACE alone for patients with HCC at different stages [18,19]. However, the efficacy of TACE-Iodine 125 in early-and intermediate-stage HCC is still unclear.…”
Section: Introductionmentioning
confidence: 99%